Peranan kesepian sebagai moderator antara distres psikologis dengan kesejahteraan psikologis mahasiswa selama pandemi COVID-19: The role of loneliness as a moderator between psychological distress and the psychological well-being of students during the COVID-19 pandemic - Nurdiyanto, F A; Harjanti, Enggar Putri; Laban, Rinekso Wismanto (Persona:Jurnal Psikologi Indonesia, 2022)
The COVID-19 pandemic threatens students' psychological well-being. Distress and loneliness are prevalent psychological problems related to mobility restriction and "stay-at-home" instruction. University students are vulnerable to dealing with mental health problems and experience a decrease in psychological well-being during the pandemic. This study was to examine whether loneliness plays a moderating role in relationships between distress and psychological well-being. This research was conducted in the context of the COVID-19 pandemic and evaluated how loneliness and distress affect students' well-being since then. A total of 747 students (female = 566, Mage = 20,2 years) participated through the purposive technique. We used three instruments: the Kessler Psychological Distress Scale (α=0,926), the UCLA Loneliness Scale (α=0,722), and the Warwick-Edinburgh Mental Well-Being Scale (α=0,932). Our moderation analysis showed that psychological distress significantly decreased psychological well-being (F = 306, p < 0,01). The role of loneliness as a moderator in the relationship between distress and psychological well-being also showed a significant moderation model (F = 161, p < 0,01). Loneliness contributes to a decrease in students' psychological well-being who experience psychological distress. Keywords: Psychological well-being, loneliness, psychological distress, university students Abstrak Pandemi COVID-19 mengancam kesejahteraan psikologis mahasiswa. Distres psikologis dan kesepian merupakan masalah psikologis yang berkaitan dengan pembatasan mobilitas dan instruksi stay at home. Selama masa pandemi, mahasiswa rentan terhadap masalah psikologis dan mengalami penurunan kesejahteraan psikologis. Penelitian ini dimaksudkan untuk menguji apakah kesepian berperan sebagai moderasi dalam hubungan antara distres dan kesejahteraan psikologis mahasiswa. Penelitian ini dilakukan pada konteks pandemi COVID-19 dan berupaya melihat bagaimana pengaruh kesepian dan distres pada kesejahteraan psikologis mahasiswa. Sebanyak 747 mahasiswa (perempuan = 566, Musia = 20.2 tahun) berpartisipasi secara purposive sampling. Tiga instrumen digunakan: Kessler Psychological Distress Scale (α=0,926), UCLA Loneliness Scale (α=0,722), dan Warwick-Edinburgh Mental Well-Being Scale (α=0,932). Analisis moderasi menunjukkan bahwa distres psikologis memiliki peran signifikan dalam menurunkan kesejahteraan psikologis (F = 306, p < 0,01). Peran kesepian sebagai moderator dalam hubungan antara distres terhadap kesejahteraan psikologis juga menunjukkan model yang signifikan (F = 161, p < 0,01). Kesepian berkontribusi pada penurunan kesejahteraan psikologis pada mahasiswa yang mengalami distres psikologis. Kata kunci: Kesejahteraan psikologis, kesepian, distres psikologis, mahasiswa